2010
DOI: 10.1016/j.quascirev.2009.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium and non-sea salt sulfate in the EPICA ice cores as indicator of biological activity in the Southern Ocean

Abstract: a b s t r a c tSulfate (SO 4 2À ) and ammonium (NH 4 þ ) flux records over the last 150,000 years from both Antarctic EPICA ice cores (European Project for Ice Coring in Antarctica) are presented. The ice core record from Dome C is influenced by the Indian sector of the Southern Ocean (SO), whereas Dronning Maud Land is facing the Atlantic sector. Generally, they reflect the past atmospheric aerosol load and, thus, potentially reveal the fingerprint of marine biogenic sources from the SO. The most importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 93 publications
1
69
1
Order By: Relevance
“…Recent works suggested that black carbon, derived mostly from biomass burning, was transported to Antarctic coasts (Fiebig et al, 2009;Hara et al, 2010). Significant increase of anthropogenic species, however, have not been identified in the Antarctic ice core records (e.g., Legrand and Mayewski, 1997;Watanabe et al, 2003;Kaufmann et al, 2010) and snow pit record (Iizuka et al, 2004). Furthermore, our previous investigation showed the occasional occurrence of Antarctic haze at Syowa Station during winter-spring .…”
Section: Introductionmentioning
confidence: 85%
“…Recent works suggested that black carbon, derived mostly from biomass burning, was transported to Antarctic coasts (Fiebig et al, 2009;Hara et al, 2010). Significant increase of anthropogenic species, however, have not been identified in the Antarctic ice core records (e.g., Legrand and Mayewski, 1997;Watanabe et al, 2003;Kaufmann et al, 2010) and snow pit record (Iizuka et al, 2004). Furthermore, our previous investigation showed the occasional occurrence of Antarctic haze at Syowa Station during winter-spring .…”
Section: Introductionmentioning
confidence: 85%
“…They are also unusual among measured chemicals in that the concentration recorded over a full glacial cycle in two cores [55] is inversely proportional to the snow accumulation rate, such that the flux is almost constant. Only non-sea-salt sulfate shows a similarly flat flux over such major climate shifts.…”
Section: The Long Perspective: Ammoniummentioning
confidence: 96%
“…Hence, ammonia is supposed to be the major neutralizer agent for acidic species, especially sulfuric and nitric acids, and it plays a relevant role as pH-regulator in the marine boundary layer (MBL), as first proposed by Bouwman et al (1997). Indeed, NH 4 + and sulfate are often associated in the atmospheric aerosol because they arise from marine activity (Kaufmann et al, 2010). In off-shore oceanic areas, NH 4 + mainly originates from the biological decomposition of organic matter, with a highly variable contribution of zooplankton, as well (Johnson (2008) recently developed the concept of "co-emission", suggesting interaction processes between nssSO 4 2− and NH 4 + in the MBL.…”
Section: Ion Balancementioning
confidence: 99%